Pelatihan Penulisan Bahasa Iklan dan Strategi Promosi di Masa Pandemi - Dian Susanthi I Gusti Ayu Agung; Mirsa Umiyati; Kiky Nurwahyuni (Postgraduated Community Service Journal, 2021)
In this Community Service, there are two areas of problems faced by small entrepreneurs on Akasia’s street, namely the micro and macro fields. Microeconomics usually analyzes specific economic problems, for example companies or institutions, while macroeconomics usually studies more complex problems, such as public finances. Micro problems faced by small entrepreneurs on Akasia’s street are promotional media such as damaged and unmaintained banners, lack of media or promotional advice such as print or online media, the solution offered is to repair banners and design and create several promotional media such as banners, logos, brochures , business cards and WA Business, Facebook and Instagram. As for the macro problems faced, namely awareness of the importance of advertising languages as promotional media is still very minimal, lack of awareness of the importance of using print and online-based media in promoting the goods/services offered. So, the solution to this problem is to socialize to traders about persuasive advertising languages as a medium.